An Analysis of Eco Trends Content Framing in Digital Environmental Communication on PILI Green Network's Instagram - Maeva Ziyadatun Nafi'ah; Hari Otang Sasmita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The increasing complexity of global environmental crises requires effective digital communication strategies to build public awareness. This study aims to analyze the environmental issues presented and the framing patterns used in EcoTrends content on the Instagram account @piligreennetwork managed by PILI Green Network. This research employed a descriptive qualitative method using Robert Entman’s (1993) framing analysis approach. Data were collected through observations of 22 EcoTrends contents published between February 2024 and January 2026, as well as in-depth interviews with three key informants involved in content production. The findings show that EcoTrends covers six categories of environmental issues, namely ecological disasters, climate and weather phenomena, environmental governance and policy, conservation and biodiversity, sustainable lifestyles, and current viral issues. The framing analysis reveals that EcoTrends applies a consistent communication pattern by presenting trending issues, explaining their ecological causes, building moral judgments, and providing calls to action or solutions for audiences. Entman’s four framing elements are integrated through visual, narrative, and textual dimensions. This study concludes that EcoTrends not only delivers information about environmental crises but also constructs public understanding of ecological issues through communication strategies that adapt to digital trends.